Mobile Devices in an Introductory Programming Course. - Mahmoud, Ousay H.; Dyer, Allan (Computer (00189162), 2008)
This article discusses strategies for teaching computer science students how to develop programs on a desktop platform, such as Microsoft (MS) Windows, that will run on a portable platform such as the Java Platform, Micro Edition (Java ME). The authors use Java ME to develop applications for the BlackBerry, a smartphone made by Research in Motion Ltd. These exercises are designed to encourage the students to develop applications for their own phones and to encourage them to think about how smartphone programming changes the interface and interaction models used in programming. The article also notes that the University of Guelph in Ontario, Canada is developing curricula around the programming of smartphones through their Centre for Mobile Education Research.